2017
DOI: 10.1016/j.brat.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A prospective examination of risk factors in the development of intrusions following a trauma analog

Abstract: Several factors have been linked to the severity of posttraumatic distress, although retrospective designs in much of the literature limit conclusions regarding the temporal relation between risk factors and corresponding symptoms. To address these concerns, the current project employed an analog trauma paradigm to assess the impact of background characteristics, stress response, and post-stressor affect regulation on subjective distress and intrusive memories experienced during the subsequent processing of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…2 Previous experience with trauma may have taught these individuals that intrusive symptoms are to be expected -unpleasant but not necessarily threatening -and that hypervigilance is both distressing and ultimately counter-productive. That intrusive thoughts are specifically linked to sympathetic activation has been demonstrated using an analog trauma paradigm, which found that increased skin conductance (a marker of sympathetic activity) during presentation of a distressing film clip was associated with greater frequency of intrusions afterward (40). A prospective, longitudinal emergency department study in which skin conductance response (SCR) data was gathered within h of a real-life trauma event demonstrated that SCR magnitude significantly predicted which individuals would go on to develop chronic PTSD, lasting at least 1 year (41).…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous experience with trauma may have taught these individuals that intrusive symptoms are to be expected -unpleasant but not necessarily threatening -and that hypervigilance is both distressing and ultimately counter-productive. That intrusive thoughts are specifically linked to sympathetic activation has been demonstrated using an analog trauma paradigm, which found that increased skin conductance (a marker of sympathetic activity) during presentation of a distressing film clip was associated with greater frequency of intrusions afterward (40). A prospective, longitudinal emergency department study in which skin conductance response (SCR) data was gathered within h of a real-life trauma event demonstrated that SCR magnitude significantly predicted which individuals would go on to develop chronic PTSD, lasting at least 1 year (41).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, changes in state psychological factors such as those discussed above are usually accompanied by physiological stress responses (e.g., changes in skin conductance). For example, both greater mood change and higher physiological reactivity have been found to predict more intrusions immediately after an aversive film ( Ripley, Clapp, & Beck, 2017 ) and also in the 24 h after a virtual reality analogue trauma (an unexpected emergency situation simulated in an underground parking lot; Schweizer et al, 2017 ). In women, lower heart rate variability (regarded as a sign of less adaption to environmental changes) prior to watching a stressful film predicted more intrusive memories of the film ( Rombold-Bruehl et al, 2017 ), while peri-film decreases in heart rate predicted the frequency of image-based (rather than verbal) intrusive memories ( Chou, La Marca, Steptoe, & Brewin, 2014b ) (see also Holmes, Brewin, & Hennessy, 2004 ).…”
Section: Insights From Cognitive Science On the Development Of Intrusmentioning
confidence: 99%
“…TFP-studies indicated that similar vulnerability factors underlie the development of stress-related symptoms as in PTSD and ASD patients (Ripley, Clapp, & Beck, 2017). Pre-risk factors as maladaptive coping strategies (Davis & Clark, 1998;Regambal & Alden, 2009), higher levels of trait anxiety, depressive symptoms, trait dissociation and higher vividness of general mental imagery are related to higher intrusive memory frequency upon trauma induction (James et al, 2016).…”
Section: Introductionmentioning
confidence: 96%